1994
DOI: 10.1144/pygs.50.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Triassic sandy braidplain and aeolian sedimentation in the Sherwood Sandstone Group of the Sellafield area, west Cumbria

Abstract: SUMMARY During the Permo-Triassic the Sellafield area formed part of the eastern margin to the East Irish Sea Basin. Basin-margin alluvial fan, shallow marine and coastal mudflat sedimentation created a locally thick Permian succession. Triassic sediments are represented by the Sherwood Sandstone Group, which comprises the St Bees, Calder and Ormskirk sandstone formations. The basal few metres of the St Bees Sandstone are characterized by sheetflood sandstones, interbedded with playa-mudflat deposits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 40 publications
3
40
0
Order By: Relevance
“…Channel fills with erosive bases are accompanied by lateral and mid-channel bar forms showing a mixture of lateral and downstream accretion. A braided river interpretation is concordant with observations by other authors for the lower part of the Sherwood Sandstone elsewhere in the UK and Ireland: Northwest England (Burley, 1984;Jones and Ambrose, 1994), East Irish Sea Basin (Cowan, 1993;1993b;Meadows and Beach 1993a), Southern…”
Section: Channel Element -Chsupporting
confidence: 91%
“…Channel fills with erosive bases are accompanied by lateral and mid-channel bar forms showing a mixture of lateral and downstream accretion. A braided river interpretation is concordant with observations by other authors for the lower part of the Sherwood Sandstone elsewhere in the UK and Ireland: Northwest England (Burley, 1984;Jones and Ambrose, 1994), East Irish Sea Basin (Cowan, 1993;1993b;Meadows and Beach 1993a), Southern…”
Section: Channel Element -Chsupporting
confidence: 91%
“…The base of the Mercia Mudstone Group in Arran may be isochronous with part of the Sherwood Sandstone Group in the Vale of Eden and Solway Firth (Lovell 1983). This is consistent with a northward migration of the St Bees Sandstone Formation (Jones andAmbrose 1994, Holliday et al 2001). Correlation between the Triassic basins of Scotland, England and Ireland is very difficult due to the range in thicknesses and lack of continuity of lithological units (Taylor et al 1971), however, Lovell (1983 showed the Rathlin, Arran and Ulster Basins as being interconnected.…”
Section: Comm) It Is a Relief Cast Of The Left Pes And Includes Digsupporting
confidence: 71%
“…This northward palaeocurrent appears to extend north even as far as the Cumbrian coast, on the NW margin of the East Irish Sea Basin (Jones & Ambrose, 1994).…”
mentioning
confidence: 89%